Clinical Trial Registration and Reporting: Drug Therapy and Prevention of Cardiac-Related Infections - Ma, Lin-Lu; Qiu, Yang; Song, Mei-Na; Chen, Yun; Qu, Jian-Xin; Li, Bing-Hui; Zhao, Ming-Juan; Liu, Xin-Can (Frontiers in Pharmacology, 2019)
Objective Clinical trials are the source of evidence. ClinicalTrials.gov is valuable for analyzing current conditions. Currently, the state of drug interventions for heart infections is unknown. The purpose of this study was to comprehensively assess the characteristics of cardiac-related infection trials and the status of drug interventions. Methods The website ClinicalTrials.gov was used to query all registered clinical trials on drug interventions for cardiac-related infections as of February 16, 2019. All registration studies were collected, regardless of their recruitment status, research results, and research type. Registration information, results and weblink-publications of those trials were analyzed. Results A total of 45 eligible trials were evaluated and 86.7% of them began from 2008 or later while 91.1% of them mainly adopted interventional study type. Of all trails, 35.6% were completed and 15.6% terminated. Besides, 62.2% of interventional clinical trials recruited more than 100 subjects. Meanwhile, 86.7% of the eligible trials included adult subjects only. Of intervention trials, 65.8% were in the third or fourth phase; 78.1% adopted randomized parallel assignment, with 2 groups; 53.6% were masking, and 61.0% described treatment. Moreover, 41.5% of the trials were conducted in North America while 29.3% in Europe. Sponsors for 40.0% of the studies were from the industry. Furthermore, 48.9% of the trials mentioned data monitoring committees, 24.4% have been published online, and 13.3% have uploaded their results. Drugs for treatments mainly contained antibiotics, among which Glycopeptides, β-lactams and Lipopeptides were the most commonly studied ones in experimental group, while Glycopeptides were more common for prevention in the experimental group. Additionally, 16.2% of the trials evaluated new antimicrobials. Conclusions Most clinical trials on cardiac-related infections registered at ClinicalTrials.gov were interventional RCTs for treatment. Most focused drugs were old antibiotics, and few trials reported valid results. It is necessary to strengthen supervision over the improvement of results, and to combine antibacterial activity with drug delivery regimens to achieve optimal clinical outcomes.